Polish Catholic press and political communication of the Church on the basis of the 2000-2015 presidential election - Leśniczak, Rafał (Political Preferences, 2018)
The article is an attempt to answer the question what role in political communication of the Catholic Church in Poland play the most important Polish Catholic opinion weekly magazines (Gość Niedzielny, Niedziela, Tygodnik Powszechny). Span of the analysis covers last 15 years. The research included the presidential campaign period in 2000, 2005, 2010 and 2015. The analysis was conducted with regard to the articles published during the period of one month prior to the presidential elections. The author assesses to what extent the analyzed press titles were convergent with the official announcements of the Polish Bishops' Conference regarding the political involvement of the Catholic Church. It is important to find an answer to the question of how the Catholic press supported one of the candidates for the office of President of the Republic. Another important question that needs clarification is whether and to what extent journalists discussed electoral programs of individual candidates. According to the author, the results of research regarding political engagement of Catholic press in the four presidential campaigns are a representative sample to determine the role of the analysed Catholic press in political communication of the Catholic Church in Poland. Key words: political communication, Catholic Church, presidential election, catholic press